Ordinances of the City of Bayonne, From 1869 to 1894, at 338-40 (1894) - (:unkn) unknown (My University, 1877)
An Ordinance To Regulate the Sale, Storage, and Keeping of Gunpowder and Other Explosive and Dangerous Materials Within the Limits of the City of Bayonne, 1-5: Regulated the storage and sale of gunpowder in the city of Bayonne
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER